INTERACTION OF A BACTERIAL ADENOSINE TRIPHOSPHATASE WITH PHOSPHOLIPID BILAYERS - Redwood, W. R. (1969)
A solubilized nonparticulate adenosine triphosphatase from Streptococcus fecalis spheroplast membranes (Abrams, A., and C. Baron, Biochemistry, 7,501 (1968)) interacts at pH 7.5 with lipid bilayer membranes to produce a 10(2)- to 10(4)-fold increase in the electric conductance of the bilayer. In addition, a small decrease in the electrical capacitance of the interactant system is also observed. Interaction is obtained with bilayers formed from a solution in n-decane of either purified egg phosphatidyl-choline, synthetic diphytanoyl phosphatidyl-choline, or a total extract of the membrane lipid of S. fecalis. The magnitude of the increase in conductance is dependent on the presence of Mg(++) and upon the concentrations of both Na(+) and K(+) in the range of 10(-2) to 10(-1)M. An additional tenfold increase in conductance is obtained when ATP is added to the ambient aqueous phase surrounding the bilayer ATPase interactant system. No conductance change is obtained with ATPase which has been treated with pronase. ATPase activity is dependent upon Mg(++) and upon the concentrations of Na(+) and K(+) in the region of 10(-1)M. The function of the ATPase in the intact bacterial membrane is apparently associated with the active transport of cations. The increased conductance in the bilayer which results from its interaction with the ATPase, together with the similarity between the dependence of this interaction and the dependence of ATPase activity on Mg(++), ATP, and the Na(+), K(+) concentrations suggests that the bilayer-ATPase interactant complex may be similar in structure and properties to the membrane-ATPase complex in the intact organism.